A cosmopolitan, Sami-friendly scholar? Väinö Tanner on the best way to treat the Sami - Jukka Nyyssönen (Arctic and North, 2016)
The topic of this article is Väinö Tanner’s views on Sami policies, which are examined from numerous perspectives, including his personal career and Nordic Sami policies. The discursive resources that he re-produced are also charted. Of the Sami policies in existence at that time, Tanner advocated the Swedish variant, which suited better the agenda of his scholarly production on the Skolt Sami. The origins of his choice are located in his long-term professional contact with Swedish experts on the Sami and the expert role provided by Swedish discourses on the Sami. The anti-Finnish agenda in his scholarly production, and his consequent wish to elevate the Sami in the hierarchies of that time, rendered the more aggressive Norwegian rhetoric on the Sami unusable. In addition, Tanner showed signs of a cultural sensitivity that made him suspicious of assimilative policies.